UNVEILING RISKS: IDENTIFYING WARNING SIGNS FOLLOWING BARIATRIC SURGERY - Dr. Usama Abbas; Patricio Duran S; Amgad Samir Abdelmageed Mohamed Elfeki; Anas Tifour; Ahmed Samir Abdelmageed Mohamed Elfiki; Wahaj Ayub (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Bariatric surgery is a procedure that is frequently performed as a recommended intervention for the benefit of individuals struggling with extreme excess weight, particularly when conventional weight loss methods prove ineffective. Despite its perceived safety, the procedure carries inherent risks and complications, necessitating thorough assessment and monitoring of warning signs post-surgery. Objective: A comprehensive review was the purpose of this investigation. warning signs being connected to bariatric surgery, shedding light on potential risk factors and adverse outcomes. Methods: Both the Latin American and Caribbean Literature in Health Sciences (Lilacs) database and the Medical Literature Analysis and Retrieval System Online (Medline) were utilized in the process of conducting a systematic review methodology. Following the completion of bariatric surgery, a qualitative data analysis was carried out to identify major risk factors and warning indications. Results: Several risk factors were discovered by the review contributing to unfavorable ends and surgery following bariatrics. These included genetic predisposition, anxiety, excessive consumption of sweets, psychological and a lack of control or restraint in eating, as well as disordered eating behaviors behaviors, and alterations in the volume of the stomach post-surgery. Notably, following surgery, a quick loss of weight heightened the risk about biliary problems, which may result in morbidity and call for readmission or additional surgery. Conclusion: Understanding warning signs of bariatric surgery is essential for those who are interested in clinicians and patients alike. This systematic review underscores the multifactorial nature of risks following surgery, emphasizing the importance of tailored interventions and vigilant postoperative monitoring to mitigate adverse outcomes and optimize patient safety and well-being